Can Deliberative Democracy Favor a Flourishing Relationship Between Humans and Carnivores? - Vucetich, John A.; Bruskotter, Jeremy T.; Macdonald, David W. (Frontiers in Conservation Science, 2021)
There is considerable interest in improving participatory governance in decision-making processes for the conservation of biodiversity and management of conflicts between humans and wildlife. Among the various modes of participatory governance, deliberative democracy has received virtually no attention for decisions focused on conserving biodiversity. This is surprising given that deliberative democracy is the dominant form of democratic theory and is associated with decision-making processes that have been successfully applied to a wide range of complicated decisions across diverse cultural settings. Moreover, deliberative democracy has several distinctive properties that would seem to make it well-suited for many conservation decisions. First, deliberative democracy is better-designed than other processes to handle cases where the object of conservation appears to be insufficiently valued by those who have the most detrimental impacts on its conservation. Second, deliberative democracy engenders a rich kind of representation and impartiality that is nearly impossible to achieve with participatory governance focused on managing conflicts among hyper-engaged stakeholders. Here, we review the principles of deliberative democracy, outline procedures for its application to carnivore conservation, and consider its likelihood to favor carnivore conservation.